2019
DOI: 10.1111/dth.12935
|View full text |Cite
|
Sign up to set email alerts
|

Cosmetical treatments of connective tissue disorders

Abstract: Connective tissue disorders (CTDs) are chronic inflammatory conditions that can lead to scarring and disfiguration. Although conventional methods are often of little benefit in cutaneous manifestations, the use of cosmetic procedures is still controversial. Concerns have also been raised concerning cosmetic treatments in CTDs, and particularly regarding lasers and fillers, due to photosensitivity and potential reactivation. This article reviews the cosmetic treatment of various CTDs under three headings ‐ lase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Its main advantage is the identical structure of the molecule in any living being, which minimizes the probability of immunogenicity [ 21 , 22 ]. So far, no single case of reactivation or stimulation of morphea was reported after administration of purified HA biosynthesized via bacterial fermentation [ 15 ]. The widespread use of HA in orthopaedics for intra-articular injections for many years serves as evidence of its safety profile [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Its main advantage is the identical structure of the molecule in any living being, which minimizes the probability of immunogenicity [ 21 , 22 ]. So far, no single case of reactivation or stimulation of morphea was reported after administration of purified HA biosynthesized via bacterial fermentation [ 15 ]. The widespread use of HA in orthopaedics for intra-articular injections for many years serves as evidence of its safety profile [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…The isolated columns of ablated skin do not disrupt proper healing and they stimulate collagen remodelling and decrease the level of fibrosis marker transforming growth factor beta-1 (TGFβ1). This therapy leads to the degradation of the abnormal collagen in morphea lesions and the induction of normal collagen synthesis [ 15 , 41 ]. The superiority of this method in comparison with low dose UVA-1 was observed in 17 patients in the study by Shalaby et al [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2). The authors then read each publication, and 5 were deemed irrelevant, only mentioning BT injection use in passing 45–49 . Authors were unable to obtain access to 1 publication through their institutions 50 .…”
Section: Methods Of Reviewmentioning
confidence: 99%
“…In this field, medical treatments have often proved unsatisfactory and do not meet patients’ expectations of cosmetic outcome. Thus, it seems obvious that looking for safe and effective practices that correct aesthetic and functional deficits is highly desirable [ 10 , 11 ]. Due to advances in the application of lasers and their possible beneficial effects, the aim of this study is to review the reported usage of lasers in treating morphea.…”
Section: Introductionmentioning
confidence: 99%